A dashboard to monitor housing market - Kee, Li Yap (2020)
This project is to develop a dashboard to monitor housing market. By delivering dashboard to provide at a glance information to the user. Solving the problem of difficult analysis while switching on multiple web applications. At the same time provides data for similar projects that are going to conduct in the future. The focus of the initiate project would be in Kampar. As to collect non-city data, it would bring more chances to the trend of research and development in Kampar area. Therefore, collecting data is costly and time consumed, most of the organization would not be conducting the similar analysis without resources that are ready to be accessed, especially when the main services of the organization is not on delivering data analysis. Besides, delivering dashboard having an unknown return value to the organization, develop a dashboard without resources that are ready to be accessed would be harmful and risky to an organization. This project would be a “white rat” to the market, to understand whether there are demands of delivering this type of services. Kampar, as a small town in Perak, with limited data provided on the internet, is one of the obstacles throughout conducting this project. Lastly, this project would be involved in data mining and data analytics to conduct a meaningful insight to users of the dashboard. Targeted user of the dashboard would be renters, property investors and existing landlords.